Response of Fuel Subsidy Removal as Sustainable Transport Policy (Case Study: Workers in Jakarta Metropolitan Area) - Octaviani Ariyanti; Samuel Petros Sebhatu (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
Motorization in urban areas contributes several problems such as congestion, accidents, gas emissions, noises, and infrastructure breakage. Meanwhile, most of the developing countries cannot overcome such growth activities, as well as in Jakarta. By December 2013, Vice Governor of Jakarta proposes fuel subsidy removal policy as one of sustainable transport policy. This study is intended to understand and investigate how fuel subsidy removal policy scenarios (25%, 50%, and 100%) in Jakarta affects travelers’ behavior and analyze such policy to support sustainable transport by using qualitative research methodology. Interviews and questionnaires survey is conducted to workers in Jakarta, which includes ranking scale question for traveler response options. The result shows that half of the respondents are not affected and will only respond to fuel price increasing at IDR 31,400 for gasoline price and IDR 26,300 for ADO (Auto Diesel Oil). Moreover, there is a tendency of respondent's to the response by changing their travel mode choices into more fuel efficient private vehicle.